Assessment of Laboratory Bench Cleaning Protocols with Surface Cultures - Shafaq, Humaira; Ali, Ifrah; Dojki, Maqboola; Shakoor, Sadia (Infectious Diseases Journal of Pakistan, 2023)
Background: Laboratory-acquired infections are a serious concern for the clinical microbiology laboratory worker. Laboratory workers have been reported to acquire shigellosis and salmonellosis from working in high-burden laboratories. Even the most minor breaches of protocol can result in infection as a very small infectious dose may be required. The likelihood of recovery of such organisms is highest for technologists culturing stool specimens. If routine biosafety principles are followed, contamination of bench surfaces should not occur with such organisms. Objective: We evaluated routine bench cleaning practices in at a busy clinical microbiology laboratory to determine the risk to laboratory workers. Methods: The study was carried out at the clinical microbiology laboratory of the Aga Khan University in Karachi. The laboratory processes over 100 stool specimens per day, and has standardized protocols pertaining to biosafety and bench cleaning procedures. In an effort to establish effectiveness of cleaning procedures in the laboratory we observed bench contamination by monitoring the total microbial counts (Heterotrophic plate counts – HPCs) and culturing for Shigella and Salmonella species. Results: 30 samples were collected over 1 week. HPCs were higher at the end of the work day, demonstrating the waning of bleach cleaning effectiveness. Contamination with Salmonella or Shigella spp was not observed. Conclusion: Adequate bench disinfection protocols were implemented in the study laboratory. Frequent audits of these cleaning practices instill confidence in laboratory workers that their work environment is safe.